Analisis Efesiensi Daya Penerangan Jalan Umum Tenaga Surya di Kecamatan Pulau Ternate - Idham A Djufri; Miftah Muhammad (Journal of Science and Engineering, 2021)
Solar Street Lighting a street lighting solution for areas or areas that are not within the PLN network area or for lighting efficiency using solar power. The use of public street lighting, although it has several advantages, there are still disadvantages in the field conditions, including the improper placement of the lighting so that it is blocked from sunlight, the use of inappropriate materials, unsuitable height of poles and lack of maintenance which results in not optimal utilization of solar energy. In this study, an analysis of the power efficiency of solar street lighting in the District of Ternate Island will be carried out by conducting direct observations and measurements in the field. The results showed that the maximum voltage for street lamps that were not blocked by trees was 23 volts, while those that were blocked by trees were 19 volts. The lighting strength of the street lights that are blocked by trees is 9 lux, while those that are not blocked by trees are 10 lux. The amount of input voltage for the solar panels affects the strength of the lamp lighting